Generation of cardiomyocytes from vascular adventitia-resident stem cells - Mekala, Subba Rao; Woersdoerfer, Philipp; Bauer, Jochen; Stoll, Olga; Wagner, Nicole; Reeh, Laurens; Loew, Kornelia; Eckner, Georg; Kwok, Chee Keong; Wischmeyer, Erhard; Dickinson, Mary Eleanor; Schulze, Harald; et al. (Circulation Research, 2018)
Rationale: Regeneration of lost cardiomyocytes is a fundamental unresolved problem leading to heart failure. Despite several strategies developed from intensive studies performed in the past decades, endogenous regeneration of heart tissue is still limited and presents a big challenge that needs to be overcome to serve as a successful therapeutic option for myocardial infarction. Objective: One of the essential prerequisites for cardiac regeneration is the identification of endogenous cardiomyocyte progenitors and their niche that can be targeted by new therapeutic approaches. In this context, we hypothesized that the vascular wall, which was shown to harbor different types of stem and progenitor cells, might serve as a source for cardiac progenitors. Methods and Results: We describe generation of spontaneously beating mouse aortic wall-derived cardiomyocytes without any genetic manipulation. Using aortic wall-derived cells (AoCs) of WT (wild type), αMHC (α-myosin heavy chain), and Flk1 (fetal liver kinase 1)-reporter mice and magnetic bead-associated cell sorting sorting of Flk1+ AoCs from GFP (green fluorescent protein) mice, we identified Flk1+CD (cluster of differentiation) 34+Sca-1 (stem cell antigen-1)-CD44− AoCs as the population that gives rise to aortic wall-derived cardiomyocytes. This AoC subpopulation delivered also endothelial cells and macrophages with a particular accumulation within the aortic wall-derived cardiomyocyte containing colonies. In vivo, cardiomyocyte differentiation capacity was studied by implantation of fluorescently labeled AoCs into chick embryonic heart. These cells acquired cardiomyocyte-like phenotype as shown by αSRA (α-sarcomeric actinin) expression. Furthermore, coronary adventitial Flk1+ and CD34+ cells proliferated, migrated into the myocardium after mouse myocardial infarction, and expressed Isl-1+ (insulin gene enhancer protein-1) indicative of cardiovascular progenitor potential. Conclusions: Our data suggest Flk1+CD34+ vascular adventitia-resident stem cells, including those of coronary adventitia, as a novel endogenous source for generating cardiomyocytes. This process is essentially supported by endothelial cells and macrophages. In summary, the therapeutic manipulation of coronary adventitia-resident cardiac stem and their supportive cells may open new avenues for promoting cardiac regeneration and repair after myocardial infarction and for preventing heart failure.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Coronary vessels; Macrophages; Myocardial infarction; Myocardium; Stem cells